Wearable Sensor and Internet of Things Technology for Better Medical Science: A Review - Olivia Putri, Arisa; A. M. Ali, Musab; Saad, Mohammad; Samsul Hidayat, Sidiq (International Journal of Engineering and Technology, 2018)
E-health becomes one of the internet's products for healthcare. The problems of health service such as far hospital and expensive examination fees become the emergence of this technology. Consequently, people reluctant to check their health to hospital. E-health provides information on disease prevention, detecting early symptoms, and monitoring the patient's condition based on medical parameters from a far distance. Internet of things became the main concept in this system, which combines wearable sensors, communication systems, and mobile user interfaces. Reliable and valid system, easily carried, help the doctor to monitor patients from far distance expectantly to overcome the problems. The aims of this paper review are describing how an internet of things technology and wearable sensor help medical science and find the best way to create a health monitoring system.Â Â Â